PENGEMBANGAN DAN PEMANFAATAN BAHAN AJAR E-MODUL DALAM PROSES PEMBELAJARAN - Dedeh Descindang Irnissa; Anggita Lestari; Aa Rahmawati; Hermawan Wahyu Setiadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of digital technology has driven significant changes in the learning process, one of which is through the use of e-modules as alternative, more interactive and flexible teaching materials. This study aims to examine the development, characteristics, and utilization of e-modules in improving the quality of learning. The method used was a literature study by collecting and analyzing various relevant journals, books, and scientific publications. The results of the study indicate that e-modules have self-instructional, self-contained, stand-alone, adaptive, and user-friendly characteristics, thus supporting independent learning and facilitating students to achieve learning objectives optimally. E-modules have been proven to have a positive impact in terms of increased motivation, learning independence, effective learning outcomes, and ease of access. However, several challenges were also identified, such as limited access to devices, low student digital literacy, high demands for learning discipline, and the need for teacher competency in digital media development. Overall, the use of e-modules has great potential to support learning in the Independent Curriculum, especially in efforts to increase creativity, digital literacy, and student independence.